Bilingual and monolingual adults learning an additional language: ERPs reveal differences in syntactic processing. Issue 5 (2nd October 2017) - GREY, SARAH; SANZ, CRISTINA; MORGAN-SHORT, KARA; ULLMAN, MICHAEL T.
Abstract : It has been suggested that bilinguals learn additional languages 'better' than monolinguals. However, evidence is sparse, particularly for grammar. We examined behavioral and neural correlates of learning an additional (artificial) language in early Mandarin–English bilinguals, compared to English monolinguals. Following grammar instruction, participants practiced comprehension and production, and judged grammaticality at low and high proficiency while event-related potentials (ERPs) were acquired. Bilinguals and monolinguals did not differ on behavioral measures, but showed distinct ERP patterns. At low proficiency only bilinguals showed a P600, a common ERP correlate of syntactic processing in native speakers of languages. At high proficiency both groups showed P600s, though the monolinguals also evidenced an anterior positivity not typically found in native speakers of languages during syntactic processing. These findings suggest that, even without bilingual/monolingual behavioral differences, bilinguals show ERP patterns for an additional language that are more similar to those of native speakers of languages.